Body Language Signals, Social Class, and Implicit Bias. (2nd October 2021) - Henry, Sue Ellen; Feuerstein, Abe
Abstract: Markers of social class are communicated and interpreted through a diverse set of social practices. With the strategies presented here, teachers can recognize the signals of social class and work to interrupt implicit bias.